Utilizing AI in Digital Learning: The Role of Metacognitive Reasoning, Organizational Support, and Socioeconomic Status in Enhancing Academic Performance through Intrinsic Motivation - Awalia, Andi Dio Nurul; Rosidah; M.Miftach Fakhri; Della Fadhilatunisa (Jurusan Teknik Informatika dan Komputer, 2026)
Purpose – This study examines how metacognitive reasoning, organizational support, and socioeconomic status shape academic performance through the mediating role of intrinsic motivation in an artificial intelligence (AI) integrated learning environment. Design – A quantitative, cross-sectional design was employed. Data from 373 university students were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate relationships among the constructs. Findings – Metacognitive reasoning and organizational support significantly increased intrinsic motivation, which in turn positively affected academic performance. By contrast, socioeconomic status did not significantly influence intrinsic motivation or academic performance. Research implications – The results underscore the importance of cognitive and contextual supports in fostering student motivation and achievement. The nonsignificant effects of socioeconomic status warrant further investigation; future studies should explore additional individual and environmental factors that may shape academic outcomes in AI-enabled learning settings. Originality – This research advances an inclusive and effective framework for digital learning in higher education by demonstrating the central role of metacognitive skills and institutional support in designing AI-enhanced strategies that cultivate students intrinsic motivation and academic success.